Editorial: emerging issues in sociotechnical systems thinking and workplace safety - Noy, Y. Ian; Hettinger, Lawrence J.; Dainoff, Marvin J.; Carayon, Pascale; Leveson, Nancy G.; Robertson, Michelle M.; Courtney, Theodore K. (Ergonomics, 2015)
The burden of on-the-job accidents and fatalities and the harm of associated human suffering continue to present an important challenge for safety researchers and practitioners. While significant improvements have been achieved in recent decades, the workplace accident rate remains unacceptably high. This has spurred interest in the development of novel research approaches, with particular interest in the systemic influences of social/organisational and technological factors. In response, the Hopkinton Conference on Sociotechnical Systems and Safety was organised to assess the current state of knowledge in the area and to identify research priorities. Over the course of several months prior to the conference, leading international experts drafted collaborative, state-of-the-art reviews covering various aspects of sociotechnical systems and safety. These papers, presented in this special issue, cover topics ranging from the identification of key concepts and definitions to sociotechnical characteristics of safe and unsafe organisations. This paper provides an overview of the conference and introduces key themes and topics. Practitioner Summary: Sociotechnical approaches to workplace safety are intended to draw practitioners' attention to the critical influence that systemic social/organisational and technological factors exert on safety-relevant outcomes. This paper introduces major themes addressed in the Hopkinton Conference within the context of current workplace safety research and practice challenges.